Pengaruh Metode Gallery Walk Terhadap Hasil Belajar Siswa Kelas IV SDN Tladan 2 Tahun Ajaran 2020/2021 - Vivi Rulviana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Learning must be implemented using methods and media that enable students to improve their learning results. The goal of this study was to see how the Gallery Walk approach affected primary school pupils' learning outcomes. This is a study that is being conducted as an experiment. The result of this research is that the pretest value is 0.222 while the posttest value is 0.223. Based on the t-test, it shows that tcount = 14,601 with ttable = 2,228, 14.601 > 2,228, then H0 is rejected. So it can be concluded that there is an influence of the Gallery Walk learning method on the learning outcomes of elementary school students. Pelaksanaan pembelajaran memerlukan metode dan media yang dapat memfasilitasi siswa guna meningkatkan hasil belajarnya Tujuan dari peneltian berikut adalah mengetahuii pengaruh metodeeGallery Walk terhadp hasill belajar siswa SD. Penelitian berikut termasuk dalam jenis eksperimen. Hasil penelitian ini Lhitung nilai pretest sebesar 0,222 sedangkan Lhitung nilai postest 0,223. Berdasarkan uji t menunjukkan hasil_thitung = 14,601 dengan ttabel = 2,228, 14,601 > 2,228, maka H0 ditolak. Dapat disimpulkan ada pengaruh metode pembelajaran Gallery Walk terhadap hasil belajar siswa Sekolah Dasar.